Long term evolution of deep banner banks offshore Western Brittany (Iroise Sea, France): indications of a paleo-coast line and of the interaction between hydrodynamics and seafloor morphology ... - Daguinos, Paul; Le Roy, Pascal; Jouet, Gwenael; Menier, David; Le Dantec, Nicolas; Ehrhold, Axel; Prunier, Christophe; Dupont, Pauline; Franzetti, Marcaurelio (SEANOE, 2024)
This seismic dataset came from surveys carried out by the “Institut Universitaire Européen de la Mer” (IUEM, UBO) and the Ifremer, on the Iroise Sea platform, (Western Brittany, France). Two main files are provided here: -The first one is composed of the 10 seismic profiles described in the article "Long term evolution of deep banner banks offshore Western Brittany (Iroise Sea, France): indications of a paleo-coast line and of the interaction between hydrodynamics and seafloor morphology", with tiff and SEG Y / NAV data. The second is composed of SEGY files over the whole platform from several research cruises (GEOBREST (11, 12, 13, 14,15, 19), SpeeDunes, Bankable, SABASETI). .Nav files are the XY coordinates of each seismic line. For each SEGY fil there is both a non-corrected and a corrected version (name of the file finishing by PRC).Each data file is accompanied by other files with the same name (for example .GEO .PRM ...) that are necessary to open the corrected version. An integrated approach combining ...